Foraging home ranges of Black Brant Branta bernicla nigricans during spring stopover at Humboldt Bay, California, USA - Black, Jeffrey M; Lee, Derek E; Ward, David H (Wildfowl, 2013)
Foraging home ranges of Black Brant Branta bernicla nigricans (n = 8) were quantified to determine proportional use of available intertidal habitat during spring migration stopover at Humboldt Bay, California, USA. The average foraging range area was 232 ha (s.d. Â± 156 ha) of which 114 ha (s.d. Â± 43 ha) was comprised of their primary food, eelgrass Zostera marina; the other habitats included mudflat/sandbar and deep water channels. This amounted to individuals using an average of 16% of the available eelgrass in the bay (716 ha). Potential consequences are discussed for Black Brant remaining faithful to a relatively small proportion of available habitat. Individual Black Brant may employ different foraging strategies in different parts of Humboldt Bay to obtain nutrients and body stores to fuel migration and subsequent breeding.